Canvas tas/bag. SOMAFCO Mathematics Club (Solomon Mahlangu Freedom College of the African National Congress, based in Tanzania)
Canvas tas/bag. SOMAFCO Mathematics Club (Solomon Mahlangu Freedom College of the African National Congress, based in Tanzania).